2016
DOI: 10.1021/acs.langmuir.6b02035
|View full text |Cite
|
Sign up to set email alerts
|

Tin Ion Directed Morphology Evolution of Copper Sulfide Nanoparticles and Tuning of Their Plasmonic Properties via Phase Conversion

Abstract: Copper-deficient copper sulfide (Cu2-xS) nanoparticles (NPs) have been investigated as important hole-based plasmonic materials because of their size, morphology, and carrier density-dependent localized surface plasmon resonance (LSPR) properties. Morphology and carrier density are two important parameters to determine their LSPR properties. Here, we demonstrate that the foreign metal ion, Sn(4+), directs the growth of djurleite Cu31S16 from nanodisk to tetradecahedron along the [100] direction. To control the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 28 publications
1
27
0
Order By: Relevance
“…Many physical and chemical properties of these nanomaterials are dictated by the size, shape, as well as the surface structure and chemistry. Thus morphology is a crucial parameter that controls the property and functionality of the materials 5, 4549 . A number of approaches, including sol-gel synthesis 50 , template method 51 , thermal decomposition 52 , hydrothermal 53 , co-precipitation 54 , and electrodeposition 55 have been proposed for the preparation of transition metal oxides with controlled morphology and surface chemistry.…”
Section: Introductionmentioning
confidence: 99%
“…Many physical and chemical properties of these nanomaterials are dictated by the size, shape, as well as the surface structure and chemistry. Thus morphology is a crucial parameter that controls the property and functionality of the materials 5, 4549 . A number of approaches, including sol-gel synthesis 50 , template method 51 , thermal decomposition 52 , hydrothermal 53 , co-precipitation 54 , and electrodeposition 55 have been proposed for the preparation of transition metal oxides with controlled morphology and surface chemistry.…”
Section: Introductionmentioning
confidence: 99%
“…The crystal phase of Cu 2− x S NDs in Figure 4 b–d cannot be simply assigned to djurleite Cu 1.94 S in spite of the well‐matched d ‐spacing. A mixture of djurleite Cu 1.94 S and roxbyite Cu 1.8 S is more reasonable for the above Cu 2− x S NDs because both the djurleite and roxbyite share similar sulfur anion sublattices as well as formation energy [45] . Along with XRD patterns, the UV/Vis/NIR absorption spectra of Cu 2− x S NDs during the phase conversion are shown in Figure 5 b.…”
Section: Resultsmentioning
confidence: 93%
“…For crystal phase control, 1-dodecanethiol, [40] Na 2 S 2 O 3 , [41] di-tertbutyl disulfide [42] as well as crystal sulfur organic/inorganic solutions [43,44] were utilized to prepare chalcociteC u 2 S/Cu 2Àx S, djurleite Cu 1.97 S, roxbyite Cu 1.8 S, and covellite CuS with the ND being the most prevalent morphology. For morphology control, metal ions, [45] halide ions, [46] and organic surfactants [47] have been utilized to prepare djurleite Cu 1.94 St etradecahedra, covellite CuS triangular nanoprisms, and chalcocite Cu 2 S/Cu 2Àx S NRs, respectively.N evertheless, the aforementioned Cu 2Àx SN Ps were preparedi nq uite different reactionc onditions, which may unavoidably affect both of the crystal phase and morphology of the product. Therefore, preparation of Cu 2Àx SN Ps with controllable crystal phase and morphology by simple variation of reactionp arameters such as sulfur precursor reactivity is highly desired but relativelys carce.…”
Section: Introductionmentioning
confidence: 99%
“…[148,181] However, the presence of cations can also influence the shape of the NC. [182] For example Chen et al [183] demonstrated a morphological evolution of the Cu 31 S 16 nanodisks to tetradecahedra due to the Sn 4+ -directed modification of the vertical crystal planes of the copper sulfide disk seeds. This leads to the preferential deposition of the copper and sulfur source on the vertical crystal planes, favoring the formation of the tetradecahedra.…”
Section: [12]mentioning
confidence: 99%